Burden, trends, and projections of nutritional deficiencies in China from 1990 to 2030 - Chen, Bijuan; Yang, Huanhuan; Zheng, Wei; Zheng, Hanchen; Lin, Hui; Yu, Jiami; Xu, Yun; Guo, Zengqing; Zhan, Zhouwei (Frontiers in Nutrition, 2025)
BackgroundNutritional deficiencies remain a pressing public health concern, especially in countries undergoing rapid demographic and epidemiologic transitions. In China, understanding the long-term trends and sex- and age-specific burden of nutritional deficiencies is crucial for designing targeted prevention and intervention strategies.MethodsWe used data from the Global Burden of Disease Study 2021 to estimate the burden of nutritional deficiencies in China from 1990 to 2021. Indicators included incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs), stratified by age, sex, and type of malnutrition. We applied Joinpoint regression to examine temporal trends and conducted age-period-cohort (APC) and decomposition analyses to explore underlying drivers. Projections through 2030 were generated using Bayesian APC modeling.ResultsIn 2021, nutritional deficiencies led to 46.0 million incident and 146.1 million prevalent cases in China, with a significantly higher burden among women. While males had higher mortality and YLL rates, females showed higher prevalence, YLDs, and DALYs. The age-standardized burden declined substantially from 1990 to 2021, particularly for protein-energy malnutrition. DALYs declined by 92.8% for protein-energy malnutrition, and vitamin A deficiency incidence dropped by 81.2%. APC analysis revealed that younger cohorts experienced dramatically lower burdens, especially among children under 5, although older adults continued to carry a growing burden due to aging. Decomposition analysis identified epidemiologic improvements as the primary driver of reduced burden, but demographic factors like population aging mitigated these gains. Forecasts indicate further declines in disease burden through 2030, with consistently higher prevalence and DALY rates projected among females.ConclusionDespite substantial progress in reducing the burden of nutritional deficiencies in China over the past three decades, disparities persist by sex and age. Continued surveillance, alongside interventions targeting women and older adults, is essential to sustain progress and address residual gaps.